2001
DOI: 10.1111/1469-8986.3810084
|View full text |Cite
|
Sign up to set email alerts
|

Independent manipulation of stimulus change and unexpectedness dissociates indices of the orienting response

Abstract: Results obtained with the standard repetition-change paradigm of orienting research cannot be attributed unambiguously to either stimulus change or to unexpectedness. By adding announcement conditions, in which participants were told about an impending stimulus change, these two factors were disentangled. In Experiment 1, reaction times (RTs) were longer and ratings of surprise were higher with unannounced than with announced stimulus change. In contrast, larger skin conductance response (SCR) magnitudes occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
1
14
1
1
Order By: Relevance
“…These include a color change in a simple visual stimulus (e.g., Meyer, Niepel, Rudolph, & Sch€ utzwohl, 1991), the change in the voice of a speaker from male to female (Niepel, Rudolph, Sch€ utzwohl, & Meyer, 1994), the appearance of the participant's own, secretly photographed face as the last picture in a face-judgment task (Reisenzein, B€ ordgen, Holtbernd, & Matz, 2006, Exp. 6 & 7), the violation of a rule concerning the temporal sequence of the stimuli, previously induced via a rule-learning task (Horstmann & Sch€ utzwohl, 1998;Reisenzein et al, 2006, Exp. 3), and the nonoccurrence of an announced stimulus change (Niepel, 2001). Manipulation checks included in several repetition-change experiments confirmed that the stimulus changes staged in the surprise trials were not only experienced as surprising but were also perceived as unexpected by the participants.…”
Section: Qualitative Version Of the Unexpectedness-surprise Hypothesismentioning
confidence: 76%
See 4 more Smart Citations
“…These include a color change in a simple visual stimulus (e.g., Meyer, Niepel, Rudolph, & Sch€ utzwohl, 1991), the change in the voice of a speaker from male to female (Niepel, Rudolph, Sch€ utzwohl, & Meyer, 1994), the appearance of the participant's own, secretly photographed face as the last picture in a face-judgment task (Reisenzein, B€ ordgen, Holtbernd, & Matz, 2006, Exp. 6 & 7), the violation of a rule concerning the temporal sequence of the stimuli, previously induced via a rule-learning task (Horstmann & Sch€ utzwohl, 1998;Reisenzein et al, 2006, Exp. 3), and the nonoccurrence of an announced stimulus change (Niepel, 2001). Manipulation checks included in several repetition-change experiments confirmed that the stimulus changes staged in the surprise trials were not only experienced as surprising but were also perceived as unexpected by the participants.…”
Section: Qualitative Version Of the Unexpectedness-surprise Hypothesismentioning
confidence: 76%
“…The repetition-change paradigm has been used most often for this purpose. In this paradigm, which exists in many variants, participants are first exposed to a series of homogenous baseline (or "habituation") trials that serve to establish, typically but not exclusively (e.g., Horstmann & Sch€ utzwohl, 1998;Niepel, 2001) through incidental learning, a schema or set of expectations about the kind, the properties, and the temporal sequence of the stimuli that occur in the experiment. In the subsequent "surprise trial," one or more of these expectations are disconfirmed by changing one or more properties of the stimuli presented in the baseline trials or by presenting an entirely novel stimulus.…”
Section: Qualitative Version Of the Unexpectedness-surprise Hypothesismentioning
confidence: 99%
See 3 more Smart Citations